THE CORPORATE SOCIAL RESPONSIBILITY AND ITS IMPACT ON THE CUSTOMER SATISFACTION, A CASE STUDY OF A SAMPLE OF MOBILE PHONE USERS IN ALGERIA - Walid Ziadi; Youcef Tebboub; Rathi Meena (International Journal of Innovative Technologies in Social Science, 2025)
This study aims at highlighting the various social aspects regarding some issues related to social responsibility which in turn aimed at preserving the safety of society, customers and the environment in general. This led the institutions to rethink their social and environmental performance in order to satisfy the needs of society. Therefore, this type of responsibility entails the service organization carrying out a set of social processes that involve the exchange of both the social return and cost between the institution and society. This is an evidence of the efforts exerted by the mobile phone companies in Algeria to upgrade the marketing dimensions of social responsibility such as the concern for society and customers as well as protecting the available environmental resources. This study used a non-random sample of customers of mobile phone companies in Algeria, specifically in the state of Jijel. The analysis of the results was based on 120 distributed survey lists.